HUBUNGAN KETAHANAN DIRI DAN PERAN TEMAN SEBAYA DENGAN PERILAKU KESEHATAN REPRODUKSI REMAJA DI SMP NEGERI X JAKARTA SELATAN - Bebi Ayu Wulandari (2023)
dolescents as the next generation of the nation are vulnerable to deviant reproductive health behavior, which will have an impact such as, sexually transmitted diseases, unwanted pregnancy, early marriage, abortion and school dropout. This study aims to determine the relationship between self-resilience and peer role with adolescent reproductive health behavior in SMP Negeri X South Jakarta. The research design used quantitative correlational type cross-sectional approach with stratified random sampling sample collection technique.A total of 260 grade VII, VIII adolescents at SMP Negeri X South Jakarta participated in the study. Univariate data analysis using proportion test and bivariate data analysis using Chi-Square test. The results of this study are that there is a significant relationship between self-resilience and adolescent reproductive health behavior with a p-value of 0.00 (> 0.05 ) and peer roles have a relationship with adolescent reproductive health behavior with a p-value of 0.00 (> 0.05). The implications in this study show that there needs to be optimization in implementing good reproductive health behaviors for adolescents. The results of this study provide policy recommendations to the DKI Jakarta Provincial Health Office in the form of adolescent reproductive health services in school settings